Marketing and Communication Problems and Proposed Solutions for the Turkish Women’s N.G.O. Sector - Kestane, Serpil Ünal (International Journal of Social Sciences and Management, 2014)
In almost all contemporary societies the position and importance of non-governmental organizations in terms of the way they handle and solve social issues, is undeniable. Non Governmental Organizations (NGOs) are voluntary non-profit organizations that engage in many activities ranging from cultural events to health, environment, education, law, human rights issues as well as many others. Women Focused Non-Governmental Organizations (WFNGO) in Turkey are also non-profit, engaging in combating and seeking solutions for a multitude of women- related issues. As is the case with other NGOs, their main objective is to achieve social benefits. For that reason alone, “marketing” should be perceived as a commercial activity by NGOs, but all too often this important business function is considered either as a secondary purpose or one that is completely neglected. The main objective of this study is to ascertain the marketing and communication strategies WFNGO’s utilise whilst engaging in their activities and to determine the marketing problems that inform and enlighten these organizations. An additional goal is to acknowledge the achievement of their social benefits in terms of the proposals made to the WFNGO’s, finding solutions on how to increase their reach to target groups and how to use their resources more efficiently and effectively. In line with these main objectives and sub goals, a questionnaire has been developed, entitled Marketing and Communications Problems of WFNGO in Turkey. Altogether 105 organizations active in various Turkish cities have been interviewed either face-to-face or by telephone to seek answers to the questions. The resulting data has been analyzed and interpreted using the SPSS 18.00 computer software programmed. The findings of the study reveal the general structure of WFNGO’s, within the framework of the organizations reached and establish that the common problems of almost all WFNGO’s in Turkey are of a financial and organizational nature, together with bureaucratic restrictions and a shortage of suitably qualified personnel. Another important finding of this study is that Turkish WFNGO’s consider marketing to be nothing more than a ‘vending, presentation and publicity’ activity, with 66% of the organisations interviewed considering marketing to be unnecessary. The results of this study conclude that WFNGO’s, just like profit-orientated organizations, need a strategic marketing plan and they should be advised accordingly. In a literature review it is possible to find many essays, books, journals and publications on marketing activities in non-profit organizations. However, this paper is a first in relation to marketing activities for Women Focused Non Governmental Organizations. Furthermore, in line with the information and findings obtained as a result of this study, the proposals made towards marketing activities of WFNGO’s can be used as an effective guide for such organizations. DOI: http://dx.doi.org/10.3126/ijssm.v1i3.10542 Int. J. Soc. Sci. Manage. Vol.1(3) 2014: 93-102